EXPONENETIAL AND LOGARITHMIC CRANK-NICOLSON METHODS FOR SOLVING COUPLED BURGER’S EQUATIONS - M. A. H. ALJABOORI ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In this paper we apply a new methods called exponential and logarithmic Crank-Nicolson methods for solving a coupled of Burgers equations. These methods are shown that the stability and accuracy are better than of the exponential and logarithmic finite difference methods for long time. Error norms   show that the present methods are a successful numerical schemes for solving a coupled Burgers’ equations.